Extensive Orbital Exenteration in a Bitch: Correction with Subdermal Pattern Rotation Flap - Camargo, Jessica Franciele; Kretzer Carneiro, Rafael; da Rosa Pippi, Matheus; Teixeira Gonçalves, Luciana; Gomes, Cristiano; Faria Valle, Stella (Acta Scientiae Veterinariae, 2024)
Background: Reconstructive surgery techniques for dogs have been a notable increase in recent years. Managing extensive surgical wounds can be challenging for many surgeons, particularly due to limited skin mobility. For these cases, reconstructive emerges as a viable solution. Traditionally, two methods are employed in closing wounds using surgical reconstruction techniques: skin flap or grafts. In skin flap surgery, segments of skin and subcutaneous tissue with their own vascularity are used, connected through a pedicle to the donor area. This report illustrated the use of a rotation skin flap to close an extensive wound in a bitch following exenteration due to tissue damage caused by myiases. Case: A 5-year-old Mongrel bitch was referred to the Veterinary Medical Teaching Hospital (HCV) of the Universidade Federal do Rio Grande do Sul (UFRGS) after undergoing a previous exenteration surgery due to ocular myiases. The animal was referred to the HCV due to the extensive skin loss in the previous procedure, mandating reconstructive surgery. Preceding the surgery, the wound bed was managed for 2 weeks of treatment with a wet dressing with petrolatum gauze, promoting the formation of healthy granulation tissue on the wound through dressing changes every 48 h. Upon the development of granulation tissue, the wound was prepared for flap transplantation. The bitch was prepared for surgery, and the Propofol was used for anesthetic induction protocol. Firstly, the wound debridement was performed followed by the application of a polypropylene mesh graft to the orbit using nylon thread and simple interrupted sutures. A semicircular incision was made, and a flap was created from the area above the other healthy eye. The flap borders were fixed with a Backhaus towel clamp and sutured using simple interrupted and nylon thread. At the end of the procedure, the flap was iced, and a bandage was applied. The bitch received antibiotics until the course of treatment was completed. Bandage changes occurred within the initial 24 to 96 h. Around the 5th day post-surgery, a small section of the flap displayed a purple color, for which a specific therapeutic cream was applied until the color normalized. Bandage changes continued every 5 days from the 6th day until sutures were removed on the 14th day. A reexamination on the 55th day post-surgery confirmed the complete acceptance of the flap. Discussion: Reconstructive surgery is widely used in oncology surgery to address significant skin defects. However, only a small percentage of veterinarians employ reconstructive surgery for non-oncology wound-repairing procedures. This limited use of this procedure is due to limited acknowledgment of the technique. Consequently, some veterinarians opt to let wounds heal naturally, which can be time-consuming for complete healing. While the literature discusses various types of flaps, selecting an appropriate flap for extensive head skin defects should be a challenge. In this case, a rotation flap was chosen to cover the peri-orbital wound. Important to mention that the use of the flaps is not free of complications such as necrosis or dehiscence. In this case, minor post-surgical complications occurred and, both wound and the bitch were fully recovered. This suggests that employing a rotation skin flap technique can efficiently achieve rapid wound closure in the head area, minimizing infection risks and the need for extended care. Keywords: canine, eyeball orbital region, healing, reconstructive surgery, wound.